2019
DOI: 10.4103/ijpvm.ijpvm_493_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a peer-led behavioral intervention program on tobacco use-related knowledge, attitude, normative beliefs, and intention to smoke among adolescents at Iranian Public High Schools

Abstract: Background: Theory-based tobacco use prevention programs in schools were implemented to evaluate the effectiveness of this peer-led intervention on tobacco use-related knowledge, attitude, normative beliefs, and intention to tobacco use of school children aged 14–17 years old. Methods: A school-based cluster randomized controlled intervention study was conducted among 1 st , 2 nd , and 3 rd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This finding is supported by other studies [ 50 , 51 ] and emphasizes that students may be more influenced by their beliefs or the interpretation of reality than by the actual prevalence of drug use among friends [ 52 , 53 ]. Interventions aiming to increase critical thinking and fact-checking skills may help to reduce the impacts of these normative beliefs [ 19 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by other studies [ 50 , 51 ] and emphasizes that students may be more influenced by their beliefs or the interpretation of reality than by the actual prevalence of drug use among friends [ 52 , 53 ]. Interventions aiming to increase critical thinking and fact-checking skills may help to reduce the impacts of these normative beliefs [ 19 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research at Iranian public high schools showed similar result between the groups of students who were given the peer education method and the groups of students who were not given peer education according to gender. 26 Meanwhile, research on high school students in Surabaya, Indonesia shows that gender has a significant relationship with intention to participate in peer education programs in efforts to prevent drug abuse, where women have higher intentions than men. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Peers are defined as people who share similar characteristics, circumstances or experiences. Several studies have demonstrated their effectiveness in changing tobacco use behaviours among young people (Bilgiç & Günay, 2018;Ford et al, 2013;Mohammadi et al, 2019;Orsal & Ergun, 2021). To date, the evidence of the use of peer-led interventions to prevent alcohol consumption is weak and scarce, as was evidenced in a recent meta-analysis of peer-led programmes for alcohol use among youth ages 11 to 21 (Georgie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%